THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT PT. SYAUKATH SEJAHTERA GANDAPURA ACEH - Nadila Sahara; Likdanawati; A Hadi Arifin; Khairawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of Transformational Leadership, Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior at PT Syaukath Sejahtera Gandapura. The independent variables in this study are Transformational Leadership, Job Satisfaction and Organizational Commitment, while the dependent variable is Organizational Citizenship Behavior. This type of research uses a quantitative method, data collection using a questionnaire containing questions and statements by distributing it to the employees concerned at PT Syaukath Sejahtera Gandapura. The scoring technique uses a Likert scale. This research was conducted at PT Syaukath Sejahtera with 116 respondents, where the sampling in this study used saturated samples, where all populations were sampled so that the number of samples in this study was 116 respondents. This study uses multiple linear regression analysis with the SPSS (Statistical Program for Social Science) program. The results of this study indicate that transformational leadership and organizational commitment do not affect Organizational Citizenship Behavior at PT Syaukath Sejahtera Gandapura, while the job satisfaction variable has a negative and significant effect on Organizational Citizenship Behavior at PT Syaukath Sejahtera Gandapura. The better the transformational leadership and organizational commitment in a company, the more it will increase the Organizational Citizenship Behavior or extra-role behavior of employees, thereby increasing employee performance.